Sharia Supervision in The Standards of Good Governance Perspective in Libyan Islamic : الرقابة الشرعية في ضوء معايير الحوكمة الرشيدة بالمصارف الاسلامية الليبية - Mohamed Bentaher, Mesbah; Mohd Noh, Mohd Shahid; Mohamad, Mohammad Taqiuddin (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2022)
This study aims to highlight the role of Shariah Supervisory Authorities, functions and mechanisms of formation, effectively played by the principles and mechanisms of governance in increasing the efficiency of its performance, and to highlight the role and importance of legitimate governance oversight bodies in the achievement of disclosure and transparency to its business. The study found the need to provide a guiding board of directors and Shariah Supervisory Authority on how to perform their duties on the issues legitimacy guide, as well as the completion of the legal framework and raising the efficiency of the legitimate bodies, and the supervisory and control devices for Islamic Financial Institutions ‘And work on the interest of planning, monitoring and evaluating performance of the Sharia Supervisory Authority, as well as disclosure and transparency about the activities of these illegal bodies to reassure dealers, through the formulation of a framework for legitimate governance oversight bodies and circulated to Islamic financial institutions. The study clarified the important role played by the Sharia Supervisory Board, and the study presented a number of examples of the importance of the Sharia Supervisory Board in enhancing trust between Islamic banks and the public dealing with them, such as Islamic banks in Bangladesh.